(untitled) (Journal of the College of Basic Education, 2022)
The study aimed to prepare exercises compromise aimed at developing speed of the motor response and learn some basic skills of junior badminton and identify the impact of exercise interoperability in the development of motor response speed and learn the basic skills of junior badminton, the researcher used the experimental method, and design groups Almtkavitin control and experimental and included a sample Find my players Athuri Club and their number (14) for the player were divided into two groups where the control group number (7) players have made the club coach to train this group according to the curriculum subject, the experimental group’s (7) players also have been the introduction of the experimental variable of work out in the main section of the experimental group, and continued education units for two months by (8) weeks and at a rate of three units per week in the days of (Sunday, Tuesday and Thursday) to be the total number of units, educational (24) educational unit has concluded the researchers that there is evolution holds in test results Nelson response kinetic selectivity rate and motor speed of response of the arms of the members of the control group. As well as the emergence of a remarkable development in the test strike paid back to members of the control group. There is the evolution of the sum of the results of the motor speed selective response rate and test motor response speed of the arms not individuals experimental group. As well as the results of the post tests of the experimental group is better than the results of the post tests of the control group in the kinetic selectivity response rate and skill background blow paid .